CHF Phenomena by Photographic Study of Boiling Behavior due to Transient Heat Inputs - Jongdoc Park; Katsuya Fukuda; Qiusheng Liu (Science and Technology of Nuclear Installations)
The transient boiling heat transfer characteristics in a pool of water and highly wetting liquids such as ethanol and FC-72 due to an exponentially increasing heat input of various rates were investigated using the 1.0 mm diameter experimental heater shaped in a horizontal cylinder for wide ranges of pressure and subcooling. The trend of critical heat flux (CHF) values in relation to the periods was divided into three groups. The CHF belonging to the 1st group with a longer period occurs with a fully developed nucleate boiling (FDNB) heat transfer process. For the 2nd group with shorter periods, the direct transition to film boiling from non boiling occurs as an explosive boiling. The direct boiling transition at the CHF from non-boiling regime to film boiling occurred without a heat flux increase. It was confirmed that the initial boiling behavior is significantly affected by the property and the wettability of the liquid. The photographic observations on the vapor bubble behavior during transitions to film boiling were performed using a high-speed video camera system.